2003
DOI: 10.1152/ajprenal.00246.2002
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces apoptosis in renal proximal tubular cells

Abstract: II induces apoptosis in renal proximal tubular cells. Am J Physiol Renal Physiol 284: F955-F965, 2003; 10.1152/ajprenal.00246.2002-ANG II has been demonstrated to play a role in the progression of tubulointerstial injury. We studied the direct effect of ANG II on apoptosis of cultured rat renal proximal tubular epithelial cells (RPTECs). ANG II promoted RPTEC apoptosis in a dose-and time-dependent manner. This effect of ANG II was attenuated by anti-transforming growth factor (TGF)-␤ antibody. Moreover, TGF-␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 35 publications
9
112
1
3
Order By: Relevance
“…Stimulation of both AT 1 and AT 2 by Ang II has been shown to enhance apoptosis in aortic smooth 36 and renal proximal tubular cells. 37 In accordance with this finding, blockade of AT 1 with irbesartan and of AT 2 with PD123319 prevented Ang II-induced apoptosis in cultured cardiomyocytes. 35 A study in cultured cell lines that express abundant AT 2 but not AT 1 showed that AT 2 mediates apoptosis.…”
Section: Involvement Of At 2 In Apoptosis Of Vascular Smooth Muscle Csupporting
confidence: 69%
“…Stimulation of both AT 1 and AT 2 by Ang II has been shown to enhance apoptosis in aortic smooth 36 and renal proximal tubular cells. 37 In accordance with this finding, blockade of AT 1 with irbesartan and of AT 2 with PD123319 prevented Ang II-induced apoptosis in cultured cardiomyocytes. 35 A study in cultured cell lines that express abundant AT 2 but not AT 1 showed that AT 2 mediates apoptosis.…”
Section: Involvement Of At 2 In Apoptosis Of Vascular Smooth Muscle Csupporting
confidence: 69%
“…The activation of p38 MAPK is associated with the progression of renal lesion formation in various experimental models of kidney failure, including agonist-induced apoptosis in rat proximal tubular cells (17,18). Here we show that acute neomycin or gentamicin treatment stimulated the phosphorylation/activation of p38 MAPK, suggesting the initiation of a stress response in OK cells to the AGA after only 5 min.…”
Section: Discussionmentioning
confidence: 58%
“…For example, AT1R inhibitors decrease the growth of some prostate cancer cell lines and delay the development of prostate cancer, whereas AT2R inhibitors are present and have the ability to inhibit epidermal growth factor-induced prostate cancer cell growth in LNCaP and fast-growing androgen-independent PC3 cell lines (24). Increased expression of AT2R induces apoptosis in numerous cell lines, such as pheochromocytoma, fibroblasts, smooth muscle cells, and endothelial cells, with either Ang II-dependent or Ang II-independent regulation (25)(26)(27)(28)(29)(30)(31)(32). Thus, in the present study, we have determined the effects of adenoviral-induced increases in expression of AT2R on proliferation and apoptosis of prostate cancer cell lines and have addressed the potential intracellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%